2019
DOI: 10.1136/tsaco-2018-000239
|View full text |Cite
|
Sign up to set email alerts
|

Community Need Index (CNI): a simple tool to predict emergency department utilization after hospital discharge from the trauma service

Abstract: BackgroundEmergency department (ED) visits after hospital discharge may reflect failure of transition of care to the outpatient setting. Reduction of postdischarge ED utilization represents an opportunity for quality improvement and cost reduction. The Community Need Index (CNI) is a Zip code-based score that accounts for a community’s unmet needs with respect to healthcare and is publicly accessible via the internet. The purpose of this study was to determine if patient CNI score is associated with postdischa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
(20 reference statements)
2
6
0
Order By: Relevance
“…Center for Disease Control's Social Vulnerability Index was shown to be strongly associated with comorbidities in addition to being an accurate measure of surgical risk assessment. [8][9][10]21 Consistent with our findings, a 2018 single area study (focused on residents from a single county vs. nonresident patients from surrounding counties) determined that violent deaths are significantly higher in economically distressed areas by 52%, which falls within our nationwide estimates. 11 This prior study also showed that the DCI for the location of injury was a significant predictor in violent firearm events.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Center for Disease Control's Social Vulnerability Index was shown to be strongly associated with comorbidities in addition to being an accurate measure of surgical risk assessment. [8][9][10]21 Consistent with our findings, a 2018 single area study (focused on residents from a single county vs. nonresident patients from surrounding counties) determined that violent deaths are significantly higher in economically distressed areas by 52%, which falls within our nationwide estimates. 11 This prior study also showed that the DCI for the location of injury was a significant predictor in violent firearm events.…”
Section: Discussionsupporting
confidence: 87%
“…Multiple studies demonstrate the strength of existing indices regarding the identification of surgical risk, hospital discharge status, and readmission rates. [8][9][10] Prior work illustrates that distressed communities around a single trauma center predict youth gun violence and identified three census variables correlated with intentional trauma. 11,12 However, the association of social vulnerability indices with injury-related fatality rates on a broader scale remains unknown.…”
mentioning
confidence: 99%
“…20 The CNI has been used by Huang et al to predict emergency room visits after admission for trauma, demonstrating that patients with higher CNI had higher utilization of these resources after discharge. 11 Mehaffy et al have used the DCI in conjunction with the National Surgical Quality Improvement Program surgical risk calculator, demonstrating that addition of DCI to this calculator improves its performance. 12 Clearly these measures have value; however, there is no consensus with regards to which index should be used by surgeons studying outcomes disparities.…”
Section: Resultsmentioning
confidence: 99%
“…9 The SVI is not the only measure of social vulnerability that is being used in the surgical outcomes literature. [10][11][12] This study assesses the performance of the SVI as compared with three similar measures: the Area Deprivation Index (ADI), Community Needs Index (CNI), and Distressed Communities Index (DCI), which are measured at the census block group and zip code level, respectively. 3,13,14 Characteristics of the four measures are described and compared in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, 2019 census tract-level SDOH data was extracted from the Census Bureau’s American Communities Survey and were also compiled into a modified Community Needs Index (CNI), which combines independent SDOH factors into a composite measure to indicate healthcare barriers, using the methodology developed by Dignity Health. 18,19 Census tract-level SDOH and CNI data were aggregated up to the hospital service areas (HSA) as defined by the Dartmouth Atlas of Health Care (http://www.dartmouthatlas.org/) as these are more representative of a hospital’s healthcare market or community. To summarize, each record in the data table contained the hospital’s community benefit expenditures, hospital characteristics, aggregate SDOH characteristics of its service area, the CNI, and details about its PPHI for the year 2019.…”
Section: Methodsmentioning
confidence: 99%